2019
DOI: 10.1002/ente.201901057
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance and Immobilizing Mechanism of N‐doping Carbon Aerogel with Net Channel via Long‐Chain Directing for Lithium–Sulfur Battery

Abstract: A novel net channel and N‐doping carbon aerogel (CA) are successfully prepared by an in situ and facile method via polyimide (PI) inducting for lithium–sulfur (Li–S) batteries. The PI‐directing carbon aerogel (PI‐CA) presents a cross‐linked framework, abundant porosity, and a high specific surface area. PI‐CA spheres present effective immobilizing polysulfides and high loading sulfur for a Brunauer–Emmett–Teller (BET) surface area of 2039.4 m2 g−1 and N‐doping via physical and chemical adsorption. The Li–S bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Due to the unique features, including a continuous threedimensional (3D) nanonetwork, high porosity, large surface area and low bulk density, CA has been used as an ideal carbonaceous substrate to prepare carbon-based functional composites by assembling active non-carbon materials. [26][27][28][29][30][31][32][33][34][35][36][37] In this study, in order to improve the electrochemical performance of MCs with large theoretical capacity, CA is proposed as the carbonaceous substrate to composite with MCs. The synthesis strategy of CA/MC composites is illustrated in Fig.…”
Section: Fabrication and Characterization Of Ca@mcsmentioning
confidence: 99%
“…Due to the unique features, including a continuous threedimensional (3D) nanonetwork, high porosity, large surface area and low bulk density, CA has been used as an ideal carbonaceous substrate to prepare carbon-based functional composites by assembling active non-carbon materials. [26][27][28][29][30][31][32][33][34][35][36][37] In this study, in order to improve the electrochemical performance of MCs with large theoretical capacity, CA is proposed as the carbonaceous substrate to composite with MCs. The synthesis strategy of CA/MC composites is illustrated in Fig.…”
Section: Fabrication and Characterization Of Ca@mcsmentioning
confidence: 99%
“…Aerogels have recently drawn considerable attention in energy storage applications, for example, carbon-based aerogels are used both as anodes and cathodes for lithium-ion [99][100][101], lithium-sulfur [102][103][104], and sodium-ion [105,106] batteries. Alternatively, they also find use in supercapacitors [107][108][109][110][111], an example for Mxene-rGO (Ti 3 Cr 2 T x -reduced graphene oxide) aerogel is given in Fig.…”
Section: Applications Of Pdc Aerogelsmentioning
confidence: 99%
“…Furthermore, it was shown that both, the porous mesh structure of a novel N‐doped carbon aerogel with a channel‐containing framework, and the interaction between nitrogen atoms and lithium cations from lithium polysulfides, facilitate the enhanced electrochemical performance of the battery. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that both, the porous mesh structure of a novel N-doped carbon aerogel with a channel-containing framework, and the interaction between nitrogen atoms and lithium cations from lithium polysulfides, facilitate the enhanced electrochemical performance of the battery. [14] However, even using various complex procedures, the introduced nitrogen content is always low (less than 10 wt%). Therefore, high surface area with more active sites for host materials is necessary.…”
Section: Introductionmentioning
confidence: 99%